2015
DOI: 10.1002/ls.1324
|View full text |Cite
|
Sign up to set email alerts
|

A study on tribological behaviours of ZDDP in polymer thickened lubricating greases

Abstract: Zinc Dialkyl Dithiophosphate (ZDDP) is a well-known multifunctional additive for soap based lubricating greases. Polymers are being studied for their performance as lubricating grease thickeners and rheology modifiers. In this work the tribological study of ZDDP was carried out in polypropylene (PP), maleated polypropylene (mPP) and linear low density polyethylene (PE) thickened lubricating greases. Performance of lithium grease was taken as a reference. The tribological properties were evaluated using a four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Grease is recommended for gears, bearings and chains due to its good performances at high and low temperatures. A lot of additives were investigated and proven to reduce the friction and antiwear, such as molybdenum disulfide, phosphorus, oxides, sulfur, carbonate and rare earth compounds, to increase the life of the mating parts (Battez et al, 2006;Bakunin et al, 2004;Zhou et al, 2000;Qiu et al, 2001;Eduardo et al, 2015;Libo et al, 2015;Zhao et al, 2014;Xia et al, 2003;Gaiqing et al, 2014;Xiong et al, 2011;Dixena et al, 2016;Baumgart et al, 2010;. Therefore, researchers are focusing on developing grease to avoid the frictional wear which occurs between the mating bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Grease is recommended for gears, bearings and chains due to its good performances at high and low temperatures. A lot of additives were investigated and proven to reduce the friction and antiwear, such as molybdenum disulfide, phosphorus, oxides, sulfur, carbonate and rare earth compounds, to increase the life of the mating parts (Battez et al, 2006;Bakunin et al, 2004;Zhou et al, 2000;Qiu et al, 2001;Eduardo et al, 2015;Libo et al, 2015;Zhao et al, 2014;Xia et al, 2003;Gaiqing et al, 2014;Xiong et al, 2011;Dixena et al, 2016;Baumgart et al, 2010;. Therefore, researchers are focusing on developing grease to avoid the frictional wear which occurs between the mating bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is only one peak expected for the pure additives, other mechanism lead to the observation of multiple peaks: ZDDP in lubricating oils is known to exist in different conformations. [ 15–20 ] Their chemical equilibrium depends on the concentration of ZDDP and on the chemical composition of the lubricant, and it significantly influences the tribological performance. A mixture of ZDDP and MoDTP like in Grease 2 leads to a shift of the conformational equilibrium towards the conformation ‘basic’ ZDDP with a signature at 104 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the present types of thickeners in the greases adds the complexity of ZDDP-induced tribofilm formation on the steel surfaces due to the competitive interactions between ZDDP-thickener and the thickener-steel surface. For example, it was reported that adding ZDDP either in Li grease or polypropylene grease resulted in better performance than in LiC grease under the tested conditions [46,48,49]. Considering that the volume of the base oil is generally up to 70% and given that the remainder is thickener and less than 5% additives, the polarity of base oil would have stronger impact on the formation of ZDDP tribofilm, therefore, influencing the variation in tribological performance (shown in COF measurements) of the two greases as seen in reciprocating wear tests.…”
Section: Tribological Properties Of Zddp-containing Greasesmentioning
confidence: 99%